INVESTIGATION OF THE EFFECT OF SANDBLASTING WASTE TREATMENT METHOD AS NANO-SILICA ON THE COMPRESSIVE STRENGTH OF CONCRETE MORTAR - Abidin, Muhammad Zainal; Sutrisno, Wahyuniarsih; Sutrisno, Rahmat Dwi (Journal of Civil Engineering, 2023)
This study presents the effect of nano-silica (NS) from sandblasting waste as an additive on the mechanical properties of concrete mortar. The nano-silica was produced by using the sol-gel and mechanical grinding methods. In this research, nano silica material was added as an additive with a percentage varying from 0% to 5%. The results show that producing nano silica from sandblasting waste with a combination of sol-gel and mechanical grinding methods can produce an average size of 148.9 nm with 96.90% purities silica (SiO2). The compressive strength test also shows that adding NS can increase the compressive strength of the concrete. The highest compressive strength obtained from this research was. 29.76 MPa with the addition of 1% of nano-silica. This compressive strength is 37.5% higher than the control mixture.